2020
DOI: 10.1002/14651858.cd013600.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Convalescent plasma or hyperimmune immunoglobulin for people with COVID-19: a living systematic review

Abstract: Analysis 5.1. Comparison 5: Subgroup analysis: antibodies in recipients detected at baseline for the comparison of convalescent plasma versus placebo or standard care alone for individuals with moderate to severe disease, Outcome 1: All-cause mortality at up to day 28..

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
238
0
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 297 publications
(264 citation statements)
references
References 134 publications
8
238
0
10
Order By: Relevance
“…Two ongoing trials of convalescent plasma in pregnant patients with COVID-19 disease are ongoing (NCT04397757 and NCT04388527) [ 40 , 41 ]. Documented adverse effects of convalescent plasma use in the general population are rare but include febrile and allergic transfusion reactions, transfusion-related acute lung injury (TRALI), and anaphylaxis [ 42 ]. Randomized trials of remdesivir use in COVID-19 have excluded pregnant and breastfeeding women, but the medication was used without documented harm in pregnant women during the Ebola and Marburg virus epidemics [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two ongoing trials of convalescent plasma in pregnant patients with COVID-19 disease are ongoing (NCT04397757 and NCT04388527) [ 40 , 41 ]. Documented adverse effects of convalescent plasma use in the general population are rare but include febrile and allergic transfusion reactions, transfusion-related acute lung injury (TRALI), and anaphylaxis [ 42 ]. Randomized trials of remdesivir use in COVID-19 have excluded pregnant and breastfeeding women, but the medication was used without documented harm in pregnant women during the Ebola and Marburg virus epidemics [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…34 Evidence for the role of convalescent plasma in reducing the duration and severity of SARS-CoV-2 infection is still evolving. 35 It is important to be mindful of the well established adverse side effects of these medications. Hydroxychloroquine and azithromycin independently increase risk of adverse cardiac events (eg, QTinterval prolongation, ventricular tachyarrhythmia and sudden cardiac death).…”
Section: Risks Of Unproven Medicationmentioning
confidence: 99%
“…37 A Cochrane database review that included 20 studies (only one RCT) concluded that plasma therapy was of uncertain benefit. 38 Recently, itolizumab, an anti-CD6 IgG1 monoclonal antibody used for chronic plaque psoriasis, has been the first biologic to be approved by the Drug Controller General of India to treat CRS in moderate-to-severe COVID-19. However, there is little published data on this drug in COVID-19.…”
Section: Immunomodulatory Treatment In Covid-19mentioning
confidence: 99%